Influences of a Shocking News Event on Web Browsing - Koutra, Danai; Bennett, Paul; Horvitz, Eric (Proceedings of the SIGIR 2014 Workshop on Temporal, Social and Spatially-aware Information Access (TAIA'14) (This paper also appers as arXiv:1405.1486 and was later revised and extended in WWW 2015 paper of similar name.), 2014)
It has been suggested that online search and retrieval contributes to the intellectual isolation of users within their preexisting ideologies, where people’s prior views are strengthened and alternative viewpoints are infrequently encountered. This so-called “ﬁlter bubble” phenomenon has been called out as especially detrimental when it comes to dialog among people on controversial, emotionally charged topics, such as the labeling of genetically modiﬁed food, the right to bear arms, and online privacy. We seek to identify and study temporal information-seeking behavior and access to alternative versus reinforcing viewpoints following shocking, emotional, and large-scale news events. We choose for a case study to analyze search and browsing on gun control/rights, a strongly polarizing topic for both citizens and leaders of the United States. We study the period of time preceding and following a mass shooting to understand how its occurrence, follow-on discussions, and debate may have been linked to changes in the patterns of searching and browsing. For that purpose, we represent the web search and browsing behavior of the users as a Markov chain and study the transitions of the users between webpages of various views by using mobility indices.